2019
DOI: 10.1097/tp.0000000000003107
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Outcomes in Liver Transplantation for Recipients With HIV Infection in Europe and United States

Abstract: Background.-We evaluated trends and outcomes of liver transplantation (LT) recipients with/ without HIV infection. Methods.-LT recipients between 2008 and 2015 from the United Network for Organ Sharing and Organ Procurement and Transplantation Network and European Liver Transplant Registry were included. Trends and characteristics related to survival among LT recipients with HIV infection were determined.Results.-Among 73 206 LT patients, 658 (0.9%) were HIV-infected. The proportion of LT HIVinfected did not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 23 publications
0
39
1
Order By: Relevance
“…7 However, a recent study combining registry data from the United States and Europe showed that HCV decreased as an indication for LT for HIV-infected patients (from 76% to 52%) between 2008 and 2015, but the proportion of LTs performed in HIV-infected patients remained unchanged. 8 Whether an increasing burden of end-stage liver disease due to NASH and ALD, as seen in HIV-uninfected patients, is occurring in PLWH is not known. We aimed to evaluate changes in indications for LT among persons with and without HIV infection in the United States from 2008 to 2018, with a focus on temporal trends in nonviral indications for LT in HIV-infected patients, and to evaluate graft and patient outcomes during the study period.…”
Section: Ajt 1 | Introductionmentioning
confidence: 99%
“…7 However, a recent study combining registry data from the United States and Europe showed that HCV decreased as an indication for LT for HIV-infected patients (from 76% to 52%) between 2008 and 2015, but the proportion of LTs performed in HIV-infected patients remained unchanged. 8 Whether an increasing burden of end-stage liver disease due to NASH and ALD, as seen in HIV-uninfected patients, is occurring in PLWH is not known. We aimed to evaluate changes in indications for LT among persons with and without HIV infection in the United States from 2008 to 2018, with a focus on temporal trends in nonviral indications for LT in HIV-infected patients, and to evaluate graft and patient outcomes during the study period.…”
Section: Ajt 1 | Introductionmentioning
confidence: 99%
“… 14 AASLD does not have an official definite scoring system, and the Organ Procurement and Transplantation Network (commonly referred to as OPTN) is a unique system for transplantation adopted in the USA. 4 , 18 Therefore, we only evaluated the systematic training effect of LI-RADS in this study. In our study, the interobserver agreements of all radiologists for the LR category were increased after systematic training.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of recipients enabled study of the outcome and/or evolution of LT in large patient populations ( Table 1). The place of LT in the treatment of acute liver failure, alcoholic cirrhosis, HBV/HDV/ HCV related cirrhosis, HIV infected patients, NASH, primary biliary cholangitis, autoimmune hepatitis were examined [14][15][16][17][18][19][20][21][22][23][24]. A hepatocellular cancer study focused on the value of locoregional therapies and the impact of vascular invasion on outcome after transplantation [25,26].…”
Section: Large Disease-specific Studiesmentioning
confidence: 99%